RANDOMIZED, OPEN LABEL, ACTIVE CONTROLLED STUDY TO ASSESS AND COMPARE HEALTH RELATED QUALITY OF LIFE WITH MOMETASONE & FORMOTEROL VERSUS FLUTICASONE & FORMOTEROL DRY POWDER INHALER IN MILD TO MODERATE PERSISTENT ASTHMA - Bg, Parasuramalu; Chandra MR, Sathish; N, Huliraj; Gowda, Giriyanna; ., Gangaboraiah (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objectives: The present study was under taken to assess and compare the improvement in HRQoL among mild to moderate persistent asthma between Mometasone & Formoterol versus Fluticasone & Formoterol using dry powder inhaler using Asthma HRQoL questionnaire which is diseasespecific 32-item instrument including 4 domains: symptoms, emotions, exposure to environmental stimuli and activity limitations where impairments experienced during the previous 14 days and respond on 7-point scale. Methods: The present study was conducted in Preventive Medicine Unit and Chest & TB diseases OPD, KIMS & RC, Bangalore during March 2011 to February 2012. 60 patients were recruited in each group based on inclusion and exclusion criteria. PFT was done pre and post bronchodilator with Salbutamol nebulization with Spirometry. Study medications were randomized and were given for 12weeks. HRQoL questionnaire was administered before and after the medications and outcome was compared between them. Statistical test used were descriptive statistics, t- test. Results: There was a significant improvement in HRQoL from baseline to the end of 12 weeks in all domains (symptoms, emotional, exposure to environmental stimuli and activity limitations) in both the groups. The overall improvement in the HRQoL was better in Mometasone & Formoterol group compared to Fluticasone & Formoterol group but this difference was not statistically significant, which revealed both combinations were equally effective in improving HRQoL in mild to moderate persistent asthma. Conclusion: Both Mometasone & Formoterol and Fluticasone & Formoterol combinations are equally effective in improving HRQoL in mild to moderate persistent asthma patients. Keywords: Health-related quality of life, Mild to moderate persistent asthma, Dry powder inhaler.